SATURATION OF OXIHEMOGLOBIN AND RIGTH VENTRICLE / TOTAL VENTRICLE (RV/TV) RELATIONSHIP IN TWO COMMERCIAL LINES OF BROILERS RAISED AT SEA LEVEL - Salazar L., Christian (2013)
The study aimed to determine the relationship between body weight, oxyhemoglobin saturation and right ventricle/total ventricle ratio (VD/VT) in two commercial broiler lines raised at sea level. It was used 75 chicken males of Ross line (R) and 50 of Cobb Vantress line (CV). The birds were weighed on days 1, 10, 20, 30, and 40 of age. The oxyhemoglobin saturation was measured, and then, after slaughtering, the ventricle right/total ventricle ratio (VD/VT) in 25 R and 15 CV chicks on days 20, 30 and 40 was calculated. Additionally, the conversion feed index was calculated. The VD/VT ratio for CV was 0.195 ± 0.12, 0.199 ± 0.013 and 0.188 ± 0.032, and in R was 0.205 ± 0.016, 0.179 ± 0.022 and 0.245 ± 0.042 on days 20, 30 and 40 respectively, with statistical difference between lines (p<0.05). The oxyhemoglobin saturation varied between 92.06 and 95.75% without statistical difference between lines. CV chicks were heavier than R (p<0.05) until day 30. It is concluded that in the greatest period of growth, the Cobb Vantress line showed higher body weights and major VD/VT ratio, while oxygen saturation was similar to that of chicken in the Ross line, being these values within the expected values for broilers.